Full visualization and startup performance of an ammonia pulsating heat pipe - Zhihu Xue; Wei Qu; Minghui Xie (Propulsion and Power Research, 2013)
In this paper, a novel study on full visualization and startup performances of pulsating heat pipe using ammonia as working fluid are experimented. The tested pulsating heat pipe, consisting of 6 turns, is fully made of quartz glass tubes with 6 mm outer diameter and 2 mm inner diameter. The filling ratio is 70%. Wall temperature fluctuations of several key positions are recorded under a series charge of heat inputs. The visualization investigation is conducted to observe the oscillations and circulation flows with the advantage of high quality digital video camera, by which the unique thermodynamic behaviors are able to recognize and analyze more easily. The experimental results show that the startup power required by the ammonia Pulsating Heat Pipe (PHP) is very small, owing to particular identities of ammonia. It is observed that there are also some unevenly distributions in slug-train during initial and operating state. Phenomena such as circulation flows and local oscillations coupling breaking up of bubbles and formation of slugs are observed.